Rising popularity of anal intercourse and sexual risk taking: findings from two national probability studies of young Croatian adults - Ajduković, Dea (Array, 2012)
This study examined the prevalence and correlates of heterosexual anal intercourse in two national probability samples of young Croatian adults aged 18–25 years, which were collected in 2005 and 2010. The lifetime prevalence of anal intercourse increased from 27% to 36%. In multivariate analysis, reporting four or more lifetime sexual partners was the only correlate of the experience of anal intercourse that was significant among both women (odds ratios [ORs] = 1.78–3.27, P < 0.05) and men (ORs = 3.14–4.63, P < 0.01). Information about condom use at most recent anal intercourse was collected in the 2010 study wave only. Age (OR = 0.80, P < 0.05), female gender (OR = 0.29, P < 0.01), holding more negative attitudes towards condoms (OR = 0.28–0.32, P < 0.05) and reporting condom use at most recent vaginal intercourse (OR = 11.45, 95% Confidence interval [CI] = 5.68–23.06) were associated with using a condom at most recent anal intercourse. Given the substantial prevalence of anal intercourse among young heterosexual adults and considerable sexually transmitted infection/HIV risks associated with the practice, sex education programmes should promote the discussion of health risks associated with anal eroticism.